Rancang Bangun Alat Pirolisis Reaktor Tabung Bertingkat untuk Daur Ulang Sampah Plastik Polypropylene (PP) dengan Menggunakan Metode VDI 2221 - Adoe, Dominggus G. H.; Riwu, Defmit B.N.; Husein, Fuaddin B. (LONTAR Jurnal Teknik Mesin Undana (LJTMU ), 2022)
The benefits of this research are to produce fuel oil products from Polypropylene (PP) plastic waste as an alternative energy source by utilizing pyrolysis technology and increasing the economic value of unused plastic waste and as a reference for overcoming environmental pollution caused by plastic waste. The final result of this research is a detailed drawing of the tool, the design of the tool, and the results of the testing process on the tool in the form of data on the quantity of oil in each test carried out. With the VDI 2221 design method, a multilevel tube reactor pyrolysis device can be made for recycling polypropylene (PP) plastic waste with the best variant selection technique. The application of the method in this study was successfully proven by choosing concept 4 as the best concept and the concept could be made in real terms. Furthermore, the tool after testing is proven to be able to be used to produce products, as evidenced by the results of product testing in the form of oil, residue and gases